LOCAL CULTURE-BASED READING MATERIALS FOR EFL CONTEXT - Fajar Aminullah; Clarry Sada; Sudarsono Sudarsono (ICoTE Proceedings, 2019)
Teaching English to non-native learners is always a challenging task for any teacher in EFL contexts. One perpetual reason is the lack of exposure to the target language both orally and in writing. Debate continues about two opposing views on the utilization of authentic reading materials and the utilization of local-based reading. This paper attempts to defend the latter view by elaborating the potentials of local culture-based materials and their role in the EFL Classroom. This is a library research where the information is gathered from studies by other researchers. In EFL context, where the learners rarely have a direct acquaintance with native speakers, the benefits of making use of authentic reading book are not meaningful especially for the beginner level students due to the issues such as text readability, cultural understanding, and experiential input. Therefore, local culture-based reading materials are recommended to be developed since it suggests many benefits for the students in English as a Foreign Language context.